Molecular cancer cell responses to solid compressive stress and interstitial fluid pressure. Issue 6 (28th July 2021) - Purkayastha, Purboja; Jaiswal, Manish K.; Lele, Tanmay P.
Abstract: Alterations to the mechanical properties of the microenvironment are a hallmark of cancer. Elevated mechanical stresses exist in many solid tumors and elicit responses from cancer cells. Uncontrolled growth in confined environments gives rise to elevated solid compressive stress on cancer cells. Recruitment of leaky blood vessels and an absence of functioning lymphatic vessels causes a rise in the interstitial fluid pressure. Here we review the role of the cancer cell cytoskeleton and the nucleus in mediating both the initial and adaptive cancer cell response to these two types of mechanical stresses. We review how these mechanical stresses alter cancer cell functions such as proliferation, apoptosis, and migration.